Constructing the Meaning of Achieving Life Success in Broken Home Survivors in Virtual Communities - Lestari, Anggita; Nurfaizy, Ramadhan; Reza, Faisal; Midaya P, G Guci Derry (Sinergi International Journal of Communication Sciences, 2024)
The phenomenon of broken homes has been widely discussed in the current social media era along with the increasing public awareness of mental health. This study explores the lives of people who have gone through the difficult experience of a broken home. It focuses on those who listen to the podcast "Happy Broken Family" and are part of a Telegram group called "Broken Home Survivors." This research used a qualitative approach, with Alfred Schutz's phenomenological approach. Data collection methods include primary data through interviews and observations, as well as secondary data from books, journals, and documentation. The selection of informants was done using sampling, ensuring that participants had relevant knowledge on the topic. It was found that the broken home survivors felt that their success really depended on their own efforts. Many of them relate to the podcast's message about overcoming the struggles that come with having an intact family. They addressed their current situation with humor and gained positive insights from their experiences. The virtual community helped each other, providing support, but some participants mentioned missing a guiding figure to mediate their experiences. Ultimately, this study shows that people can find ways to come to terms with a broken home background and apply the positive lessons they have learned from the "Happy Broken Family" podcast and their supportive online community.